2017
DOI: 10.3390/ijms18030513
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Cell-Derived Microvesicles Induced Not Epithelial-Mesenchymal Transition but Apoptosis in Human Proximal Tubular (HK-2) Cells: Implications for Renal Impairment in Multiple Myeloma

Abstract: Renal impairment (RI) is one of the hallmarks of multiple myeloma (MM) and carries a poor prognosis. Microvesicles (MVs) are membrane vesicles and play an important role in disease progression. Here, we investigated the role of MVs derived from MM cells (MM-MVs) in RI of MM. We found that MM-MVs significantly inhibited viability and induced apoptosis, but not epithelial-mesenchymal transition in human kidney-2 (HK-2), a human renal tubular epithelial cell line. The protein levels of cleaved caspase-3, 8, and 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 40 publications
0
7
1
Order By: Relevance
“…Zhao et al reported that MVs contribute to inducing renal function impairment in MM patients, by inducing apoptosis of proximal tubular cells. 23 Furthermore, MVs derived from MM cells induce neoplastic cell proliferation 24 and stimulate angiogenesis by inducing proliferation, tube formation, IL-6 secretion and VEGF release by endothelial cells. 33 The expression and function of adenosinergic ectoenzymes have been demonstrated on exosomes derived from cancer patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhao et al reported that MVs contribute to inducing renal function impairment in MM patients, by inducing apoptosis of proximal tubular cells. 23 Furthermore, MVs derived from MM cells induce neoplastic cell proliferation 24 and stimulate angiogenesis by inducing proliferation, tube formation, IL-6 secretion and VEGF release by endothelial cells. 33 The expression and function of adenosinergic ectoenzymes have been demonstrated on exosomes derived from cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…18,19 Tumor-derived EV are reported as involved in disease progression [20][21][22] and as dampening anti-tumor immune response. 17,18 Involvement of MVs in tissue damage 23 and disease progression. 24 was recently reported in MM patients.…”
Section: Introductionmentioning
confidence: 99%
“…Sanders et al 22 reported that κ light chain protein can enter the nucleus and activate lysosomes, causing vacuoles and cell lysis, and eventually leading to apoptosis. Although there have been studies 4 showing that the cell activity of HK-2 was signi cantly decreased and apoptosis was signi cantly increased after treated with medium cultured with different MM cell lines, but renal pathogenic miRNA was found in the secretory vesicles of MM cell lines by sequencing. So whether the apoptosis of HK-2 cells is related to light-chain protein secreted by MM cell line has not been clari ed.…”
Section: Effect Of Pdtc On Secretion Of Light Chain Proteins In Myelomentioning
confidence: 97%
“…According to a study 4 , the cell viability of HK-2 cells treated with different MM cell lines was signi cantly decreased, and the apoptosis was also signi cantly increased. However, it was found by sequencing that the secretory vesicles of the MM cell line contain renal pathogenic miRNAs, and whether the apoptosis of HK-2 cells is related to the light chain protein secreted by the MM cell line has not been elucidated.It was reported that the light chain obtained in patients with end stage renal disease can enter HK-2 cells to produce su cient amount of hydrogen peroxide to stimulate the production of monocyte chemoattractant protein-1 (MCP-1), while MCP-1 is a key chemokine for proximal tubule activation 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Tumor-derived EVs from the RPMI8226 multiple myeloma cell line have been shown to be enriched in a number of potentially proapoptotic miRs and promoted apoptosis in the human renal tubular cell line HK2 (162), leading the authors to suggest that such EVs may play a role in the renal impairment observed in multiple myeloma.…”
Section: Detrimental Effects Of Ev-mediated Mir Transfer In the Kidneymentioning
confidence: 99%